Sprint training for vault: Off-season training program for 7-12yr old gymnasts - Uzunov, V. (Gym Coach, 2009)
Gymnastics coaches are well aware of the importance of a fast run-up for successful vaulting but often fail to devote sufficient time and training to this phase. The consequences of which severely disadvantaged those gymnasts who do not have a naturally fast run. The lack of attention paid to this phase in vaulting is reflected in available gymnastics specific literature, coaching clinics and workshops on vault training. The scope of this article is to present a 12 week off-season sprint training program, for preadolescent gymnasts (7-12 years of age), who have not had formal sprint training. A detailed discussion is presented on the theoretical and practical application of the key concepts to effective sprinting for vault: optimized running mechanics, start of run-up and acceleration. The methodology behind this program is based on current track and field coaching methods, scientific literature on sprinting biomechanics and preadolescence speed and strength training principles. Improving the run-up speed of young gymnast is often the single best way to improving their vault in the begining, thus the time spent in developing the gymnast sprinting ability is time well invested. A well designed and effective sprint training program has benefits not only for improving the vaulting potential of a gymnast, but also servers as a great lower body strength, power, coordination, agility, and plyometric training program for preadolescent gymnast, without many of the potential risks of injury often attributed too more intense plyometric programs.